LACK OF GLOBAL STANDARDS FOR SYSTEMATIZATION AND INNOVATIVE MANAGEMENT OF LOCAL BUSINESSES IN UZBEKISTAN - Sarvar Nuriddinov Xusniddin o’g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: At a time when local business systematization and innovative management processes are rapidly developing in Uzbekistan, the lack of world standards causes a number of problems in this area. Local business entities are trying to use modern management methods to effectively organize their activities and increase their competitiveness. However, the lack of international standards in this process creates many problems.